Monteiro Lobato, le maître des livres pour enfants au Brésil (1920-1945) - Tâmara Abreu (Strenae)
Monteiro Lobato (1882-1948), whose name is almost unknown in France, is nonetheless without question the dominant figure in Brazilian children's literature in the interwar period and one of the founding fathers of this literary field. By exploring Lobato's life, his commitment to and work for children, this article aims to raise awareness about this essential author of Brazilian literature and culture, while examining reasons behind his limited—even non-existent presence in France.